Development and in vivo evaluation of lipid-based nanocarriers containing Jatropha isabellei dry extract from the dichloromethane fraction intended for oral treatment of arthritic diseases - Janaina Kieling Fröhlich; Priscila Aguiar Meyer; Taciane Stein; Carlos Rogério Tonussi; Elenara Lemos-Senna (Universidade de São Paulo, 2022)
Abstract In this study, a dichloromethane fraction dry extract from the underground parts of Jatropha isabellei (DFJi) was used to prepare lipid nanocarriers (LNCJi) aimed at providing the oral delivery of terpenic compounds in the treatment of arthritis. The lipid nanocarriers were prepared by the spontaneous emulsification method. The lipid nanocarriers displayed sizes ranging from 180 to 200 nm and zeta potential values of around -18 mV. A high value of entrapment efficiency (> 90%) was obtained for jatrophone, which was used as the chemical marker of DFJi. LNCJi stored at 4°C were demonstrated to be stable through measurements of transmitted light after analytical centrifugation of the samples. In vitro drug release studies conducted in biorelevant dissolution media demonstrated that jatrophone release was faster from LNCJi than from free DFJi. When tested in an acute arthritis model, the LNCJi exhibited antinociceptive properties after oral administration of a 50 mg/kg dose, unlike the free DFJi, although no reduction in articular diameter was observed. These results suggest that an increase in the oral absorption of DFJi constituents may have occurred through the carrying of this fraction in LNCJi, thus improving the antinociceptive activity of this compound.